'It was peers and playgrounds that were missing, not play': young children in Northern Indian homes during the pandemic. Issue 4 (2nd October 2021) - Chaudhary, Nandita; Kapoor, Shraddha; Pillai, Punya
ABSTRACT: Play during early years gives rhythm to children's lives, and although we make many investments in children's play in our modern world, it is also true that children play under all conditions, even the most difficult ones. In recent times, social encounters and physical mobility have become impacted, and fear and uncertainty have become constant companions. In this article, we explore children's play during the pandemic through a series of interviews with adults and children in Northern Indian families, to understand the ways in which their activities had changed. We found that socio-economic context played a key role in defining how and how much children's play had been impacted and reported. Whereas the vocal middle-class, educated parent recounted many adjustments and anxieties, semi-urban, rural, and urban poor families mostly believed that their children played as usual, slipping out onto the street to play with other children by avoiding scrutiny.